AB0271 EFFECTIVENESS OF DULOXETINE FOR RELIEF OF THE REMNANT PAIN OF RHEUMATOID ARTHRITIS PATIENT WHOSE DISEASE ACTIVITY IS REMISSION. (2nd June 2020) - Yoshii, I.
Abstract : Background: Pain control in rheumatoid arthritis (RA) patient is an important matter. When pain remains even disease activity is remission, it causes deterioration of activity in daily living (ADL) in past research. In other words, pain affects ADL independently from disease activity, namely the Health Assessment Questionnaire (HAQ) score, a most popular index of ADL for patient with RA[1]. Thus, burden of remnant pain despite clinical remission in RA is serious and pending subject. Duloxetine, a potent reuptake inhibitor of serotonin and norepinephrine, is developed for the treatment of major depressive disorder [2]. It's effectiveness for pain relief with osteoarthritis is also widely accepted. This drug should be effective not only for chronic pain due to osteoarthritis, but also due to RA. However, effectiveness of duloxetine for remnant pain relief in patient with RA in clinical remission is still unclear. Objectives: In this study, effectiveness of duloxetine for the remnant pain despite clinical remission in patient with RA was statistically evaluated. Methods: RA patients whose pain score with visual analog scale (PS-VAS) >30mm despite Clinical Disease Activity Score (CDAI) is <2.8, were picked up for the study. These patients were divided into groups whether duloxetine was administrated (a group without duloxetine: G-C; a group with duloxetine: G-D). PS-VAS, C-reactive protein, CDAI and simplified disease activity index (SDAI), modified Health Assessment Questionnaire (mHAQ), and QOL value which is calculated from Euro-QOL 5-Dimensions (EQ-5D) were measured at the initiation of duloxetine in the G-D and at the first CDAI remission attained in the G-C, and at week 12 thereafter. Change of these indices were compared with One sample T-test for each group. Patient's global assessment (PGA) at baseline compared to the other components of CDAI was evaluated for each group statistically with One-tailed T-test. Differences between the two groups at each moment were statistically evaluated with Mann-Whitney U-test. Statistical significance was set less than 1%. All statistical analyses were performed using StatPlus:mac ® (AnalystSoft Inc., Walnut, CA, USA). Results: A total of three hundred and six patients were recruited. G-D counted sixty-eight with 18 males and 50 females, while G-C counted 238 with 57 males and 181 females. Average age were 71.3 and 71.5 for G-D and G-C, respectively, with 53.6 months for time span from baseline to initiation in the G-D. 80.8% of the patients in G-D sustained to administrate duloxetine. PGA was 0.6 and 0.5 for G-D and G-C respectively, while the other component of CDAI were below 0.3 in average for both groups and these values were significantly lower than the PGA score in both groups. PS-VAS was 46.4 and 44.0, and significantly decreased to 26.1 and 36.0 in average for G-D and G-C respectively at week 12 when compared to baseline. Reversely, the CDAI score was significantly elevated significantly from 1.16 and 1.19 to 3.25 and 4.34 for G-D and G-C respectively. PGA also significantly increased to 1.5 and 2.4 for G-D and G-C respectively. CRP and the SDAI score also demonstrated same trend significantly as the CDAI score for both groups. mHAQ decreased significantly from 0.430 and 0.495 to 0.393 and 0.487 for G-D and G-C respectively. QOL value increased from 0.800 and 0.817 to 0.811 and 0.840 for G-D and G-C respectively, however no statistical significance demonstrated in both groups. Conclusion: Duloxetine has been suggested to have effectiveness for the pain relief, for improvement of ADL, and for the contribution to QOL maintenance, however, no effect of disease activity control is expected. References: [1]Yoshii I, Chijiwa T, Sawada N. Influence of pain score measured by a visual analog scale (PS-VAS) on the Health Assessment Questionnaire Disability Index and 28-joint Disease Activity Index with C-reactive protein in rheumatoid arthritis patients. Int J Rheum Dis 2018;21:1955-61. [2]Knadler MP, Lobo E, Chappell J, Bergstrom R. Duloxetine. Clin Pharmacokinet 2011;50:281-94. Disclosure of Interests: None declared